Democracy and Financial Order: Legal Perspectives (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, Veröffentlichungen des Max-Planck-Instituts für ausländisches öffentliches Recht und Völkerrecht, 2018)
This book discusses the relationship between democracy and the financial order from various legal perspectives. Each of the nine contributions adopts a unique perspective on the legal and political challenges brought to the fore by the Global Financial Crisis. This crisis and the ensuing sovereign debt crisis in Europe are only the latest in a long series of financial crises around the globe in recent decades. By their very existence, but also as a result of the political turmoil they have created, these financial crises testify to the well-known tensions between democracy and a market-based economic and financial order. However, what is missing in this debate is an analysis of the role of law for reconciling democracy with a market-based financial order. To fill this lacuna, the book focuses on the controversy surrounding the concept of law, thereby adding another variable to the debate on the relation between democracy and capitalism. Each chapter addresses the concept of law from a particular theoretical angle, be it a full-grown legal theory or an approach in political economy that has a particular view of the law.